ANALISIS PROSES PERUMUSAN VISI, MISI, DAN NILAI DALAM PENGEMBANGAN IDENTITAS LEMBAGA PENDIDIKAN - Alamsyahbani; Sofia, Syahwa; Asti, Tria; Hidayat, Rara Saphira; Firyansah, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the formulation of the vision, mission and values at SDIT Ash-Shidiqi Jambi City. The main focus of this study is to understand the process of formulating the vision, mission, and values carried out by the school, and how these three elements reflect the identity and educational goals to be achieved. The research method used is a descriptive qualitative study with data collection techniques in the form of in-depth interviews, observation, and documentation. The results of the study indicate that the formulation of the vision, mission, and values at SDIT Ash-Shidiqi involved the participation of various parties, including the principal, teachers, parents, and the committee. The formulated vision reflects the goal of creating a generation that is noble, creative, independent, knowledgeable, and digitally proficient. The school's mission covers various aspects, including character development, fostering student religiosity, and developing digital technology. The values held by the school focus on honesty, responsibility, and cooperation. Thus, the formulation of the vision, mission, and values at SDIT Ash-Shidiqi, Jambi City is an important foundation in determining the direction of education and optimizing student character development.